The Safe Bag / Nur Yasmin Muhamad Raffin - Muhamad Raffin, Nur Yasmin (2020)
This company Melur Sdn Bhd. was founded in 2016 and our business is focusing on produce good quality luggage that will satisfy the need of our customers. The product of our company is the “SAFE BAG”. The objective of producing this bag to give extra safety and protection towards the bag that will ensure customers will relax and enjoy the trip. The target customer for our product is for traveler and business traveler. Although we still new in the market, our product has shown its ability as a quality and fulfill the need of the customer as we were able to collaborate with one of the biggest brands in the world’s that is FILA. The total market size in 2018 is 3600 units but it has increased to 90000 units in 2020. In the next three years 2021, 2022, and 2023, we expect our market share will increase to 20%, 35% and 45 % respectively. We compete directly Universal Traveler, Samsonite, and Merax. Before we enter the market, the market share hold by our competitors is 55%, 30%, and 15% respectively. However, after we have entered the market, we able to 10% of the market share. We anticipate new companies to enter this market as we will be able to push ourselves further by a healthy competition with our competitors.